PERENCANAAN STRUKTUR ATAS GEDUNG KULIAH UNIVERSITAS MOHAMMAD NATSIR BUKITTINGGI - George Wira Sanjani; Helga Yermadona; Deddy Kurniawan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The Muhammad Natsir University Lecture Building, Bukittinggi, was built on three floors. This college building is located in the city of Bukittinggi. The structure of this building is designed to be earthquake resistant so that it uses the Special Moment Resistant Frame System (SRPMK), SNI2847:2019. The analysis of the structure of the building starts from the preliminary design, calculation of loads and working forces, calculation of reinforcement dimensions and analysis of the strength of the structure. Calculation of working forces using the Etabs application version 18. After the dimensions and the amount of reinforcement in the structural elements are obtained, it is continued with the description of the building structure. Based on the analysis that has been done, the dimensions of the column used are 350x400 mm with 12D19 mm principal reinforcement and 10–150 mm shear reinforcement. For beams, there are 5 types with the longest span of 6 m using beam dimensions of 300x400 mm with the main reinforcement at the support 7D19 mm and 5D19 mm in the field, while the shear reinforcement uses D10–125 mm at the support and 10–150 mm in the field. In the ring beam there are also 5 types with the longest span of 6 m, the dimensions of the beam ring used are 300x400 mm with 7D13 mm main reinforcement and 8-200 mm shear reinforcement and 8-250 in the field. For Floor Plate thickness 120 mm with reinforcement D10-110 mm. Keywords: Special Moment Bearing Frame System (SRPMK), SNI 2847:2019, Etabs version 18, structural elements, structures